The Manifestation of Classism in the Astro Boy Animation - Yessi Ratna Sari; Genta Iverstika Gempita (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2020)
Utopia is an appropriate word to describe about the ideal, worthy, and perfect life depicted in a city called Metro City in the Astro Boy animation. This study examines the animation movie Astro Boy and how the world that is being told in the works could be defined as Utopian world like it is being described through the movie. The purpose of this study is to proof whether the setting successfully conveyed the Utopian world or whether it still has some deficiency as Utopian is known as impossibly perfect world to be created. The corpus of this study is the movie of Astro Boy focuses on the setting and relationship between human kind and robots. This research uses a qualitative descriptive method which describes social phenomena by conducting in-depth understanding and analysis. The aims of this research is to analyze more deeply the picture contained in the animation, which shows how humans and robots are able to create a new world also coexist. Moreover, the conceptual framework that will be use is the theory of Capitalism and Classism in order to examine the setting of Utopian world.